HUKUM BOM BUNUH DIRI MENURUT ISLAM RADIKAL DAN ISLAM MODERAT - Hambali, Yoyo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2010)
Imam Samudra published a jailhouse autobiography, Aku Melawan Teroris. In his autobiography, Imam Samudra explains his justification for the Bali attracts, which killed 202 people, most of them foreign tourists. Imam Samudra argues fellow Muslim radicals to take the holy war (jihad fi sabilillah). According to him, the main duty of Muslims is jihad in the name of Allah, to raise arms against the infidels, especially now the United States and its allies. Some of moderate Moslems scholars criticize the Samara?s concept of jihad and his justification Bali?s bombing. Muhammad Haniff Hassan, a researcher at Nan yang Technology University, Singapore, writes his book Unlicensed to Kill: Countering Imam Samudra?s Justification for the Bali Bombing (Singapore, 2005). The primary objective of this book is to provide a map of Imam Samudra's thinking behind Bali bombing I as written in his book Aku Melawan Teroris to those who are not able to read the book in its original Indonesian language with an assumption that counter ideological effort cannot be executed effectively without understanding the ideas held by terrorism perpetrators. The other moderate Moslem scholar?s Gamal al-Banna and Yusuf Qaradawi also explain about the concept of jihad. According to Gamal al-Banna in his book, Jihad, jihad in the means of war is not relevant in this modern time. Yusuf Qardhawi his monumental book, Fiqh Jihad has condemned attacks on all civilians except within Israel. He denies that Palestinian suicide bombing attacks constitute terrorism. Qaradawi has suggested the legitimate use of suicide bombings against enemy combatants in modern times if the defending combatants had no other means of self-defense.